Saúde mental dos internos de medicina e médicos recém-formados: lições da pandemia de COVID-19 - Ferreira, Lis Campos (2022)
Introduction: The COVID-19 pandemic has resulted in emotional distress worldwide. Newly graduated doctors are often on the front lines of COVID-19 patient care. The medical interns also felt the impact of the situation, either because of the interruption of their academic activities, or because of the possibility of postponing or anticipating their graduation. Objectives: To describe aspects of mental health and lessons from the COVID-19 pandemic among newly graduated doctors and medical students. Methods: This is a quali-quantitative study carried out in two moments, the first in April (M1) and the second in September (M2) of 2020, using forms on a digital platform. All interns (fifth and sixth years of medical school) and physicians graduated from 2018 to 2020 from the three medical schools in the state of Sergipe were invited, and sociodemographic data, information on mental health history, presence of anxious symptoms and fears related to COVID-19 were collected, as well as open-response questions about learnings from the pandemic. Results: 335 forms were answered in April (M1) and 148 in September (M2). Alcohol consumption among physicians graduated in 2020 increased from 50% to 85% during the pandemic (p = 0.04). Psychiatric diagnosis was reported by 38.5% of the participants and use of psychotropic drugs by 30.1% of them at the beginning of the pandemic, especially those who lived alone (p = 0.03) and the single ones (p = 0.01). In addition, 88.9% of participants considered themselves exposed to excess information about COVID-19, which was associated with anxiety symptoms (p = 0.04). When asked about the main lessons learned from the pandemic, six months after it was declared, 28% of the participants' responses included patience, the unpredictability of the future and resilience in facing adversity. Approximately 42% (n=62) of the participants knew at least one person who died from COVID-19, and this was associated with the felt need to enjoy the moment and people (p<0.01). Conclusions: A high frequency of alcohol consumption was evidenced among medical students and newly graduated doctors during the COVID-19 pandemic. A history of self-reported psychiatric illness was present in a third of the sample at the beginning of the pandemic. Exposure to excess information about COVID-19 was associated with the presence of anxiety symptoms. As main lessons learned from the pandemic, patience, unpredictability of the future and resilience in facing adversity were highlighted.